Pengaruh Partisipasi Penganggaran pada Kinerja Manajerial dengan Komitmen Organisasi dan Gaya Kepemimpinan sebagai Variabel Moderating - Yeni Andriani (Universitas Jember, 2016)
BRI Unit Se-Kanca Jember is one element and an important indicator in management control systems in budgeting, BRI is divided into several liability as a center of business units each have a role in engagement budgeting and BRI involve certain parts in the preparation of the budget. The issue raised is how participation pengagaran positive and significant, the organization may moderate the relationship between participatory budgeting and how leadership style may moderate the relationship between participatory budgeting at PT. BRI Unit Se-kanca Jember. This study aims to re-examine the effect of participation on managerial performance budgeting by using these moderating variables, in addition to the research conducted to find empirical evidence about the relationship budgetary participation and managerial performance and influence organizational commitment and leadership styles on the relationship budgetary participation and managerial performance. The data was collected by distributing questionnaires. The hypothesis testing is done is a simple linear analysis and Moderated Regression Analysis. The results of this study indicate that the first hypothesis test results showed an effect of participation on managerial performance budgeting. The second hypothesis test results showed significant moderating effect of organizational commitment capable of budgeting participation on managerial performance, and the third hypothesis test results showed that leadership style moderates the relationship budgetary participation and managerial performance. Keywords: Participation in Budgeting, Organizational Commitment, Leadership Style, Managerial Performance.